Dehulling the African Yam Bean (Sphenostylis stenocarpa Hochst. ex A. Rich) Seeds : Any Nutritional Importance? Note I (Bangladesh Journal of Scientific and Industrial Research, 2007)
The flour from three colour varieties of dehulled seeds and hull of the African Yam bean (AYB) (Sphenostylis stenocarpa) were analysed for proximate composition, ash solubility and alkalinity and the mineral composition, The dehulled seeds were labelled A2, B2 and C2 while the corresponding hulls were labelled A3, B3 and C3 respectively. Both protein and carbohydrate were highly concentrated in the dehulled samples while crude fat and crude fibre were more concentrated in the hulls. The ash was more than 90 % soluble in dilute mineral acid and significant correlation existed (0.99) in the ash solubility characteristics. With the exception of phosphorus and potassium, other minerals determined (Cu, Zn, Co, Na, Ca, Mg, Mn, Fe) were found to be more concentrated in the hulls than in dehulled samples and correlation coefficients were significantly high among the samples with values ranging between 0.94 (r A2 A3, r B2 B3) and 0.95 (r C2 C3) at α= 0.05. Error of prediction of relationship between dehulled and hull samples was low in the seed fractions, ash analysis and mineral composition. These results showed that dehulling of AYB can cause a reduction in its nutritional qualities. Bangladesh J. Sci. Ind. Res. 42(2), 163-174, 2007